Albert Camus and the Pied-Noir’s failure of vision in french algeria - Nadia Abdul Samad (2011)
Albert Camus was a French citizen born from generations of settlers in Algeria. The Nobel Laureate was raised in impoverished conditions in the town of Belcourt, and he eventually left his birth country for France in his adult years amidst his troubling political position regarding the Algerian revolutionist wars for independence from colonial France. Conor Cruise O’Brien writes that “Camus’ predicament as a pied noir [was] consciously frozen in historical immobility and incapable of directly confronting the problem of the European-Arab relation” (qtd. in Kulkarni 1528). Camus was divided between preserving his right to remain in Algeria as a pied-noir and simultaneously putting an end to the exploitation which the colonised Algerians have been subjected to. This conflict of interest is revealed inexplicitly by Camus in his fiction and lyrical essays, where he admits that his ideal Algeria – which accommodates both European settlers and Algerian natives – is purely a mythical conception. On top of the generalist colonialist attitude that he has adopted, Camus’s keen following of the existentialist movement has shaped his humanistic ideals on how post-colonial Algeria should be. But alas, his detachment from both France and Algeria surfaces in his work while proving that he is unable to recognise the end of the French empire in Algeria.